Preseodymium(III) and Samarium(III) Complexes with p-(Methoxy or Chloro) Phenylglyoxal N,N-dimethyl thiosemicarbazones - THAKUR, B.G.; KR. JHA, RANJEET; KANT CHOUDHARY, RAJESH (Asian Journal of Chemistry, 2010)
Praseodymium(III) and samarium(III) complexes with p-methoxy phenylglyoxal N,N-dimethyl thiosemicarbazone and p-chloro phenyl glyoxal N,N-dimethyl thiosemicarbazone of composition [ML2(CH3COO)2]CH3COO where HL = respective thiosemicarbazone ligand have been prepared and characterized by electrical conductance, magnetic susceptibility measurements, UV, ESR and IR studies.